2009
DOI: 10.1007/s00264-009-0855-5
|View full text |Cite
|
Sign up to set email alerts
|

To what extent does leg length discrepancy impair motor activity in patients after total hip arthroplasty?

Abstract: The aim of this study was to evaluate the effects of limb lengthening up to 20 mm after THA on symmetry of hip kinematics and kinetics during common activities of daily living. Twenty patients (age range 49-80 years) operated on with Link Lubinus II THA, with lateral access and a mean follow-up of 16 months, were assessed by gait analysis during level walking, stair ascending and descending. The time-distance, hip kinetics and kinematics values were statistically compared between the operated side and the non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 21 publications
1
30
1
2
Order By: Relevance
“…Therefore, the shortening of the operated leg in this study population did not seem to compromise the prosthetic stability. Other studies reported no influence of LLD on the functional outcome after THA [11,12,32]. Accordingly, we conclude that replacement of the diseased painful joint, keeping the leg length as it was before the operation or restoring to the contralateral leg length, with correct prosthetic positioning, is associated with the best WOMAC index and prosthetic stability.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Therefore, the shortening of the operated leg in this study population did not seem to compromise the prosthetic stability. Other studies reported no influence of LLD on the functional outcome after THA [11,12,32]. Accordingly, we conclude that replacement of the diseased painful joint, keeping the leg length as it was before the operation or restoring to the contralateral leg length, with correct prosthetic positioning, is associated with the best WOMAC index and prosthetic stability.…”
Section: Discussionsupporting
confidence: 54%
“…In the literature, LLD is reported to vary widely among studies e.g. However, the threshold at which an LLD is clinically important is still a matter of debate [12,13]. However, the threshold at which an LLD is clinically important is still a matter of debate [12,13].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, although the left-right differences in gait parameters seem small, research in patients after total hip arthroplasty for osteoarthritis has indicated that these subtle difference have clinical relevance. 24 …”
Section: Discussionmentioning
confidence: 99%